George Yurii Shevelov as a Historian of the Ukrainian Language - Zhemakovs'kyi, Andrii (East/West, 2023)
An introduction to the English-language translation of an article authored by Iurii Shevel'ov (George Y. Shevelov) on the origins of the Ukrainian language.